Lipid droplets: A dynamic organelle through the growth phases of Malassezia spp (2021)
The genus Malassezia has been associated with human and animal skin microbiota, dermatological conditions, and even systemic infections. This yeast is lipid dependent, so the sources of lipids available in the medium are essential for its survival and the development of its cellular functions. Lipid droplets (LDs) are structures responsible for storing neutral lipids and are involved with various biological roles in animals, fungi, plants, and bacteria, with a relevant role in lipid metabolic processes in cells. We study the dynamics (size and number) of LDs through growth phases in five Malassezia species using the laser scanning confocal fluorescence microscopy co-staining technique. We were able to show significant differences in the parameters analyzed between the different Malassezia spp.